ONLINE TRUST IN THE CONTEXT OF GLOBAL MIGRATION: MOBILITY, SOCIALITY, AND THE PRODUCTION OF CHINESE DIASPORIC SUBJECTIVITY IN AUSTRALIA - Wang, Wilfred Yang; Zhao, Xinyu; Chen, Xu; Yang, Yanan Jana (AoIR Selected Papers of Internet Research, 2019)
In light of the conference theme, Trust in the system, this panel brings together three papers that explore the (trans)formation of Chinese diasporic subjectivity through the intellectual lens of online dis/trust. As Gidden (2010) argues, trust is a shared social reality. Such a sense of collectively is being ‘stretched’ across national borders and cultural boundaries. Fewer explore the dis/trust and the associated concepts of authenticity and credibility against a transnational and cross-border environment. By transnationality, we refer to the increased level of mobility of the material goods, financial capitals and social networks of contemporary migrants. In other words, they live a life that is constantly ‘transiting’ between national, social and cultural borders rather than having to choose a static sense of belonging. The three papers are then, organised to explore the transnational characters of Chinese migrants’ lives in Australia, from financial and economic survival to dating and socialisation, and the re-exploration of selfhood and belonging at later life. The three papers draw on different research methods range from ethnographic interviews and participant observation to the online walkthrough method and interface studies, and to the researcher embedded approach, to form critical inquiries about the production of trust in a digital era from the perspective of transnational migrations. In examining the different stages of life and the plurality of Chinese migrants in Australia, this panel has the potential to contribute to the broader conversation in online trusts in a global, polymedia era.